In-Flight Sexual Victimization in the #METOO Era: A Content Analysis of Media Reports - Lucas, Kweilin T. (American journal of criminal justice, 2021)
According to the Federal Bureau of Investigation (FBI), incidents of in-flight sexual assaults have increased in recent years, however, data and details of sexual misconduct that occur on commercial flights are difficult to obtain, particularly in situations that involve non-forcible sexual offenses. Therefore, it is unknown if sexual misconduct is increasing, or if people are reporting incidents more than they have in the past. It is also challenging to assess airline responses to sexual misconduct since there is no universal policy that clearly lays out what crew ought to do in situations that involve sexual victimization. Regardless of these shortcomings, this phenomenon is timely and worthy of exploration given the noticeable lack of criminological literature on the topic. Fortunately, in-flight sexual victimization has been given more widespread public attention by way of media reports and the #MeToo movement, and the federal government has created a task force to investigate allegations and give policy recommendations when sexual offenses occur. In light of the progressive changes that have arisen in recent years to address sexual misconduct, this exploratory study aims to highlight the poorly reported and ill-regulated problem of sexual victimization that occurs during air travel through a content analysis of online media reports to describe risk factors for in-flight victimization. Findings indicate that the physical and social characteristics of commercial flights present potential risk factors for both forcible and non-forcible sexual victimization. Practical and theoretical implications of these results are discussed.